A method for preparing high-strength powder sintered foil
By sintering on the aluminum foil substrate using nano-aluminum alloy powder and specific ingredients, the existing sintered foil is solved, and high-strength, dense structure and excellent conductivity are achieved, making high-performance capacitors easy to make.
Patent Information
- Application Number
- CN202411949823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing methods of preparing sintered foils by sintering aluminum powder or other metal powders on the surface of the aluminum foil substrate are insufficient in strength, loose structure, and easy to lose powder, affecting dielectric properties.
Nanoaluminum alloy powder is used for sintering. Through the combination of specific raw materials and preparation methods, the nanopowder is not prone to agglomeration and uniform particle size distribution. Combined with sodium polyacrylate, phosphate and tricalcium aluminate hexahydrate, etc., a steric hindered layer and chemical bond are formed to improve the density and bond strength of the sintered foil.
It significantly improves the mechanical strength and conductivity of the sintered foil, reduces powder loss, enhances dielectric performance, and facilitates the production of high-performance capacitors.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sintered foils, and in particular to a method for preparing a high-strength powder sintered foil. Background Art
[0002] Capacitors are electronic components composed of two adjacent and insulated conductors used to store electrical energy. Capacitors can store electrical energy efficiently and release it quickly when needed. They have significant advantages in circuits that require fast charging and discharging. They also have the characteristics of high power density, long service life, and a wide operating range. As an important electronic component, aluminum electrolytic capacitors are widely used in home appliances such as mobile phones and televisions, and can be used as a power source for hybrid vehicles, as well as in aerospace and other fields.
[0003] Capacitor sintered foil is a high-performance material formed by firmly combining aluminum powder or other metal powder with an aluminum foil substrate through a specific sintering process. Sintered foil is usually used as anode foil for aluminum electrolytic capacitors and has excellent properties such as high specific capacitance and high energy storage density.
[0004] However, the existing method of preparing sintered foil by sintering aluminum powder or other metal powder on the surface of an aluminum foil substrate has insufficient strength and a loose structure, which not only easily causes the sintered foil to shed powder, but also affects the dielectric properties of the sintered foil. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a method for preparing a high-strength powder sintered foil, which uses nano-aluminum alloy powder for sintering. By matching specific raw materials and preparation methods, the nano-powder is not easy to agglomerate and the particle size distribution is more uniform. At the same time, the strength and dielectric properties of the sintered foil are improved, which is convenient for making capacitors.
[0006] In a first aspect, the present invention provides a method for preparing a high-strength sintered powder foil, which is achieved by the following technical solutions:
[0007] A method for preparing a high-strength powder sintered foil comprises the following steps:
[0008] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder, smelting for 2-5 hours, pouring into nonylphenol polyoxyethylene ether solution for water quenching, and filtering to obtain aluminum alloy fragments;
[0009] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), grinding, and drying to obtain nano aluminum alloy powder;
[0010] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in a protective gas to obtain a high-strength powder sintered foil;
[0011] Wherein, the weight ratio of the oxidation-resistant aluminum powder, nano zinc powder, vanadium powder and magnesium powder in step (1) is (60-80):(5-10):(1-2):(3-5);
[0012] The weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate in step (2) is (60-70):(10-15):(1-3).
[0013] A method for preparing a high-strength sintered powder foil according to an embodiment of the present application has at least the following beneficial effects:
[0014] The high-strength sintered foil of the present application is sintered using nano-aluminum alloy powder. The nano-powder has the characteristics of small particle size, large specific surface area, and high surface activity. During the sintering process, it can more fully fill the pores and firmly combine with the aluminum foil base material, thereby improving the density of the sintered body. The use of nano-powder can also optimize the microstructure of the sintered foil, thereby improving the mechanical strength and conductivity of the sintered foil.
[0015] The present application comprises the steps of mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder, smelting and water quenching. The smelting can accelerate the mutual mixing process of the raw materials, change the mass transfer mechanism from solid phase diffusion to liquid phase flow, promote mass transfer, and water quenching can quickly cool the alloy material after smelting, which helps to improve the strength and hardness of the alloy. Nonylphenol polyoxyethylene ether can improve the wettability and dispersibility of the alloy material, thereby improving the water quenching effect. The oxidation-resistant aluminum powder can reduce the adverse effects of aluminum oxide film on aluminum alloy and improve the performance of aluminum alloy.
[0016] The sodium polyacrylate of the present application forms a steric hindrance layer on the surface of the nano aluminum alloy powder particles through intermolecular interactions. This steric hindrance effect can effectively prevent the aggregation of particles, significantly improve their dispersibility, and make the structure of the sintered sintered foil more stable and dense, thereby improving the comprehensive performance of the sintered foil.
[0017] The phosphate ester of the present application can be adsorbed on the surface of powder particles, change their surface properties, reduce the attraction between particles, thereby preventing coagulation and agglomeration between particles, and can also maintain the dispersed state of the particles, thereby improving the stabilization effect on nano-aluminum alloy powders.
[0018] The tricalcium aluminate hexahydrate of the present application is used as a binder. The tricalcium aluminate hexahydrate undergoes a hydration reaction in water or a humid environment to form stable hydration products. These hydration products have strong adhesion, can wet and adsorb on the surface of the nano-aluminum alloy powder and the aluminum foil substrate, form a chemical bond between the nano-aluminum alloy powder and the aluminum foil substrate, and tightly bond the nano-aluminum alloy powder and the aluminum foil substrate together. After compaction and molding, the hydration product of the tricalcium aluminate hexahydrate will gradually solidify. Through sintering, a hard alloy layer with a dense structure is formed between the nano-aluminum alloy powder and the aluminum foil substrate, further improving the strength and durability of the sintered foil.
[0019] According to some embodiments of the present application, the preparation of the oxidation-resistant aluminum powder in step (1) includes the following steps: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with inert gas, using rolling steel balls to crush the aluminum blocks to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder.
[0020] On the one hand, tea polyphenols can scavenge free radicals and reduce the occurrence of oxidation reactions. At the same time, tea polyphenols can coordinate with aluminum ions to form stable complexes, reduce the contact between aluminum and oxygen, and thus slow down the oxidation of aluminum powder.
[0021] Furthermore, the tea polyphenol antioxidant is prepared by mixing tea polyphenol and phosphoric acid in a weight ratio of (8-12):1.
[0022] Furthermore, the inert gas is selected from one of nitrogen, helium, neon and argon.
[0023] According to some embodiments of the present application, the average particle size of the nano zinc powder in step (1) is 15 nm. Nano zinc powder of this particle size helps to lower the smelting temperature, reduce energy consumption, improve the fluidity of the melt, make the smelting process smoother, and reduce smelting time and cost.
[0024] According to some embodiments of the present application, the smelting in step (1) is heated by intermittent heating. Intermittent heating makes it easy to control the heating time and interval during the smelting process, so that the material has an appropriate cooling time in the molten state, thereby avoiding quality instability caused by overheating. Through intermittent heating, it can be ensured that the material has sufficient time to diffuse and mix during the smelting process, making the composition more uniform and improving the overall quality of the aluminum alloy.
[0025] Furthermore, the intermittent heating is stopped for 10 minutes every 20-30 minutes.
[0026] Furthermore, the heating temperatures during the intermittent heating are 700° C., 500° C., and 300° C., respectively, and the heating is cycled sequentially after each pause.
[0027] According to some embodiments of the present application, the grinding in step (2) is wet ball milling.
[0028] Furthermore, the rotation speed of the wet ball mill is 300-600 r / min; further 300-550 r / min.
[0029] Furthermore, the wet ball milling time is 5-10 hours; furthermore, 6-8 hours.
[0030] According to some embodiments of the present application, step (2) further includes screening after the grinding.
[0031] Furthermore, the screening is used to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm. This particle size can better balance the sinterability and fluidity of the nano aluminum alloy powder, and is more conducive to improving the mechanical properties of the sintered foil.
[0032] According to some embodiments of the present application, the weight ratio of the nano aluminum alloy powder, tricalcium aluminate hexahydrate and water in step (3) is (50-60):(8-10):(10-15).
[0033] According to some embodiments of the present application, the sintering temperature in step (3) is 550-650°C.
[0034] According to some embodiments of the present application, the sintering time in step (3) is 1-3 hours.
[0035] According to some embodiments of the present application, the protective gas in step (3) is selected from one of nitrogen, helium, neon and argon.
[0036] In a second aspect, an embodiment of the present application provides a high-strength sintered powder foil manufactured by using the above-mentioned method for preparing a high-strength sintered powder foil.
[0037] The high-strength powder sintered foil according to the embodiment of the present application has at least the following beneficial effects:
[0038] The high-strength powder sintered foil of the present application has a dense structure, high strength, and good electrical conductivity, and is convenient for making capacitors.
[0039] In a third aspect, the present application provides an application of the high-strength powder sintered foil in manufacturing capacitors. The capacitors manufactured using the high-strength powder sintered foil of the present application have high capacitance, fast charge and discharge, strong structure, and good stability in use. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0041] Example 1
[0042] Preparation of high strength powder sintered foil:
[0043] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:8:1.5:4, smelting for 3.5 hours by intermittent heating, stopping heating for 10 minutes every 25 minutes, and heating at temperatures of 700°C, 500°C and 300°C respectively, and cycling in sequence after each interval. After smelting, pouring into a nonylphenol polyoxyethylene ether solution for water quenching, filtering to obtain aluminum alloy fragments;
[0044] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 450 r / min for 7 h, sieving to control the particle size distribution range of nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0045] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 55:9:13, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in helium at 600° C. for 2 hours to obtain a high-strength powder sintered foil;
[0046] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 65:12:2;
[0047] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 10:1;
[0048] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0049] Example 2
[0050] Preparation of high strength powder sintered foil:
[0051] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 60:10:1:5, smelting for 2 hours by intermittent heating, stopping heating for 10 minutes every 30 minutes, and heating at temperatures of 700°C, 500°C and 300°C respectively, and cycling in sequence after each interval. After smelting, pouring into a nonylphenol polyoxyethylene ether solution for water quenching, filtering to obtain aluminum alloy fragments;
[0052] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 300 r / min for 10 h, sieving to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0053] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 50:10:10, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in nitrogen at 650° C. for 1 hour to obtain a high-strength powder sintered foil;
[0054] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 70:10:3;
[0055] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with argon gas, using the rolling steel balls to crush the aluminum blocks to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 8:1;
[0056] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0057] Example 3
[0058] Preparation of high strength powder sintered foil:
[0059] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 80:5:2:3, smelting for 5 hours by intermittent heating, stopping heating for 10 minutes after every 20 minutes of heating, and heating at temperatures of 700°C, 500°C and 300°C respectively, and cycling in sequence after each interval. After smelting, pouring into a nonylphenol polyoxyethylene ether solution for water quenching, and filtering to obtain aluminum alloy fragments;
[0060] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 600 r / min for 5 h, sieving to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0061] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 60:8:15, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in neon gas at a temperature of 550° C. for 3 hours to obtain a high-strength powder sintered foil;
[0062] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 60:15:1;
[0063] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with helium, using the rolling steel balls to crush the aluminum blocks to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 12:1;
[0064] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0065] Example 4
[0066] Preparation of high strength powder sintered foil:
[0067] (1) The oxidation-resistant aluminum powder is mixed with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:9:1:4, and smelted by intermittent heating for 4 hours. The heating is stopped for 10 minutes every 25 minutes. The heating temperatures are 700°C, 500°C and 300°C respectively. The mixture is cycled in sequence after each pause. After smelting, the mixture is poured into a nonylphenol polyoxyethylene ether solution for water quenching, and filtered to obtain aluminum alloy fragments.
[0068] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 550 r / min for 6 h, sieving to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0069] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 54:9:13, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in argon at a temperature of 610° C. for 2 hours to obtain a high-strength powder sintered foil;
[0070] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 65:14:2;
[0071] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen, using the rolling steel balls to crush the aluminum blocks to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 9:1;
[0072] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0073] Comparative Example 1
[0074] Preparation of high strength powder sintered foil:
[0075] (1) Aluminum powder is mixed with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:8:1.5:4, and smelted for 3.5 hours by intermittent heating. The heating is stopped for 10 minutes every 25 minutes. The heating temperatures are 700°C, 500°C and 300°C respectively. The mixture is cycled in sequence after each interval. After smelting, the mixture is poured into a nonylphenol polyoxyethylene ether solution for water quenching, and filtered to obtain aluminum alloy fragments.
[0076] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 450 r / min for 7 h, sieving to control the particle size distribution range of nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0077] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 55:9:13, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in helium at 600° C. for 2 hours to obtain a high-strength powder sintered foil;
[0078] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 65:12:2;
[0079] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0080] Comparative Example 2
[0081] Preparation of high strength powder sintered foil:
[0082] (1) mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:8:1.5:4, smelting at 700° C. for 3.5 hours, pouring into a nonylphenol polyoxyethylene ether solution for water quenching after smelting, and filtering to obtain aluminum alloy fragments;
[0083] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 450 r / min for 7 h, sieving to control the particle size distribution range of nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0084] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 55:9:13, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in helium at 600° C. for 2 hours to obtain a high-strength powder sintered foil;
[0085] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 65:12:2;
[0086] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 10:1;
[0087] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0088] Comparative Example 3
[0089] Preparation of high strength powder sintered foil:
[0090] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:8:1.5:4, smelting for 3.5 hours by intermittent heating, stopping heating for 10 minutes every 25 minutes, and heating at temperatures of 700°C, 500°C and 300°C respectively, and cycling in sequence after each interval. After smelting, pouring into a nonylphenol polyoxyethylene ether solution for water quenching, filtering to obtain aluminum alloy fragments;
[0091] (2) adding phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 450 r / min for 7 h, sieving to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0092] (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water in a weight ratio of 55:9:13, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in helium at 600° C. for 2 hours to obtain a high-strength powder sintered foil;
[0093] Wherein, the weight ratio of the aluminum alloy fragments to the phosphate ester in step (2) is 65:2;
[0094] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 10:1;
[0095] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0096] Comparative Example 4
[0097] Preparation of high strength powder sintered foil:
[0098] (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder in a weight ratio of 70:8:1.5:4, smelting for 3.5 hours by intermittent heating, stopping heating for 10 minutes every 25 minutes, and heating at temperatures of 700°C, 500°C and 300°C respectively, and cycling in sequence after each interval. After smelting, pouring into a nonylphenol polyoxyethylene ether solution for water quenching, filtering to obtain aluminum alloy fragments;
[0099] (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), wet ball milling at a speed of 450 r / min for 7 h, sieving to control the particle size distribution range of nano aluminum alloy powder to be 50-100 nm, and drying to obtain nano aluminum alloy powder;
[0100] (3) mixing the nano aluminum alloy powder and water in the weight ratio of 55:13 in step (2), spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in helium at 600° C. for 2 hours to obtain a high-strength powder sintered foil;
[0101] Wherein, the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate ester in step (2) is 65:12:2;
[0102] Step (1) Preparation of the oxidation-resistant aluminum powder: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; wherein the tea polyphenols antioxidant is prepared by mixing tea polyphenols and phosphoric acid in a weight ratio of 10:1;
[0103] The average particle size of the nano zinc powder in step (1) is 15 nm.
[0104] Experimental example
[0105] The high-strength powder sintered foils prepared in Examples 1-4 and Comparative Examples 1-4 were tested for compressive strength, density, stability and resistivity.
[0106] The compressive strength is tested according to the standard of GB / T 4740-1999.
[0107] Stability test: through 20℃-1200℃ cycle 10 times thermal shock test, calculate the powder removal rate per unit area.
[0108] The test data is shown in Table 1 below:
[0109] Table 1
[0110]
[0111] It can be seen from Table 1 that the high-strength powder sintered foils prepared in Examples 1-4 of the present application have high compressive strength, good density, low resistivity, and are not prone to powder loss due to cyclic thermal shock.
[0112] The oxidation-resistant alumina powder in the preparation raw materials of Comparative Example 1 was replaced with aluminum powder, and the rest were the same as Example 1. The compressive strength, density and thermal stability of the high-strength powder sintered foil prepared in Comparative Example 1 were reduced, and the resistivity was increased, indicating that the oxidation-resistant alumina powder of the present application is very important for the preparation of high-strength powder sintered foil. The oxidation-resistant alumina powder can reduce the adverse effects of alumina film on aluminum alloys, improve the performance of aluminum alloys, and thus improve the overall performance of the prepared sintered foil.
[0113] The smelting in the preparation method of Comparative Example 2 adopts continuous high-temperature smelting, and the rest is the same as Example 1. The compressive strength of the high-strength powder sintered foil prepared in Comparative Example 2 is significantly reduced, and the thermal stability, density and conductivity are also deteriorated. This shows that the present application can easily control the heating time and interval during the smelting process through intermittent heating, so that the material has appropriate cooling time in the molten state, thereby avoiding quality instability caused by overheating. Through intermittent heating, it can be ensured that the material has sufficient time to diffuse and mix during the smelting process, making the composition more uniform and improving the overall quality of the aluminum alloy.
[0114] The preparation raw materials of Comparative Example 3 do not contain sodium polyacrylate, and the rest are the same as Example 1. The compressive strength of the high-strength powder sintered foil prepared in Comparative Example 3 is significantly reduced, and the thermal stability, density and conductivity are also deteriorated, indicating that the sodium polyacrylate of the present application forms a steric hindrance layer on the surface of the nano-aluminum alloy powder particles through intermolecular interactions. This steric hindrance effect can effectively prevent the aggregation of particles and significantly improve its dispersibility, making the structure of the sintered sintered foil more stable and dense, thereby improving the comprehensive performance of the sintered foil.
[0115] The preparation raw materials of Comparative Example 4 do not contain tricalcium aluminate hexahydrate, and the rest are the same as Example 1. The compressive strength of the high-strength powder sintered foil prepared in Comparative Example 4 is significantly reduced, and the thermal stability, density and conductivity are also deteriorated, indicating that the tricalcium aluminate hexahydrate of the present application will undergo hydration reaction in water or in a humid environment to form stable hydration products. These hydration products have strong adhesion, can wet and adsorb on the surface of the nano-aluminum alloy powder and the aluminum foil substrate, form chemical bonds between the nano-aluminum alloy powder and the aluminum foil substrate, and tightly bond the nano-aluminum alloy powder and the aluminum foil substrate together. After compaction and molding, the hydration product of the tricalcium aluminate hexahydrate will gradually solidify. Through sintering, a hard alloy layer with a dense structure is formed between the nano-aluminum alloy powder and the aluminum foil substrate, further improving the strength and durability of the sintered foil.
[0116] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A method for preparing a high-strength powder sintered foil, characterized in that: The following steps are involved: (1) Mixing oxidation-resistant aluminum powder with nano zinc powder, vanadium powder and magnesium powder, smelting for 2-5 hours, pouring into nonylphenol polyoxyethylene ether solution for water quenching, and filtering to obtain aluminum alloy fragments; (2) adding sodium polyacrylate and phosphate to the aluminum alloy fragments of step (1), grinding, and drying to obtain nano aluminum alloy powder; (3) mixing the nano aluminum alloy powder of step (2) with tricalcium aluminate hexahydrate and water, spreading the mixture on the surface of an aluminum foil substrate, compacting the mixture, and sintering the mixture in a protective gas to obtain a high-strength powder sintered foil; Wherein, the weight ratio of the oxidation-resistant aluminum powder, nano zinc powder, vanadium powder and magnesium powder in step (1) is (60-80):(5-10):(1-2):(3-5); In step (2), the weight ratio of the aluminum alloy fragments, sodium polyacrylate and phosphate is (60-70):(10-15):(1-3); The preparation of the oxidation-resistant aluminum powder in step (1) comprises the following steps: placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with inert gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying tea polyphenols antioxidant on the surface of the aluminum powder, and drying to obtain oxidation-resistant aluminum powder; The smelting in step (1) is heated by intermittent heating; The intermittent heating is performed by stopping heating for 10 minutes after every 20-30 minutes of heating; the heating temperatures during the intermittent heating are 700° C., 500° C., and 300° C., respectively, and the heating is cycled in sequence after each pause.
2. The method for preparing a high-strength sintered powder foil according to claim 1, characterized in that: The tea polyphenol antioxidant is prepared by mixing tea polyphenol and phosphoric acid in a weight ratio of (8-12):
1.
3. The method for preparing a high-strength sintered powder foil according to claim 1, characterized in that: The average particle size of the nano zinc powder in step (1) is 15 nm.
4. The method for preparing a high-strength sintered powder foil according to claim 1, characterized in that: The grinding in step (2) is wet ball milling; the rotation speed of the wet ball milling is 300-600 r / min; and the time of the wet ball milling is 5-10 h.
5. The method for preparing a high-strength sintered powder foil according to claim 1, characterized in that: Step (2) further includes screening after the grinding to control the particle size distribution range of the nano aluminum alloy powder to be 50-100 nm.
6. The method for preparing a high-strength sintered powder foil according to claim 1, characterized in that: The sintering temperature in step (3) is 550-650° C., and / or the sintering time in step (3) is 1-3 hours.
7. A high-strength sintered powder foil manufactured by the method for preparing a high-strength sintered powder foil according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for homogenizing melts by means of cyclical phase transformations and a device for implementing same
CN102355966A
Preparation method of sintered anode material with high specific surface area and high specific volume
CN113593911A